Sensing the ionosphere with the Spire radio occultation constellation - Angling Matthew J. (EDP Sciences, 2021)
Radio occultation (RO) provides a cost-effective component of the overall sensor mix required to characterise the ionosphere over wide areas and in areas where it is not possible to deploy ground sensors. The paper describes the RO constellation that has been developed and deployed by Spire Global. This constellation and its associated ground infrastructure are now producing data that can be used to characterise the bulk ionosphere, lower ionosphere perturbations, and ionospheric scintillation.